The relationship between increased regional body fat and overactive bladder: a population-based study - Yuan-Zhuo Du; Hong-Ji Hu; Jia-Qing Yang; Qian Yuan; Rong Huang; Qian-Xi Dong; Biao Guo; Ying Cao; Ju Guo (Journal of Health, Population and Nutrition)
Abstract Background The link between regional body fat distribution and overactive bladder (OAB) in prior epidemiological research has been uncertain. Our objective is to assess the relationship between increased regional body fat and the prevalence of OAB. Methods Within this analysis, 8,084 individuals aged 20 years and older were selected from NHANES surveys conducted from 2011 to 2018. The evaluation of OAB symptoms utilized the overactive bladder symptom score (OABSS). Fat mass (FM) across various regions was quantified employing dual-energy X-ray absorptiometry, which assessed total FM, trunk FM, arm FM, and leg FM. The fat mass index (FMI) was calculated as the ratio of fat mass (kg) to the square of height (meters). Data weighting was performed in accordance with analysis guidelines. A linear logistic regression model was employed to assess the correlation between regional FMI and the occurrence of OAB. Stratified analyses were also conducted. Results The study found significant associations between total FMI and limb FMI with OAB. After adjusting for all variables in the analysis, higher total FMI (OR = 1.07, 95% CI = 1.02–1.12) was linked to an increased risk of OAB. Trunk FMI (OR = 1.12, 95% CI = 1.03–1.22), arm FMI (OR = 1.59, 95% CI = 1.20–2.10), and leg FMI (OR = 1.12, 95% CI = 1.01–1.25) demonstrated significant correlations with OAB. The weighted associations between total FMI and limb FMI with OAB incidence showed no significant differences among most subgroups. Conclusions The data indicates a correlation between higher regional FMI and increased OAB risk across different populations.